Thrombotic Events during Oral Anticoagulant Treatment: Results of the Inception-cohort, Prospective, Collaborative ISCOAT Study - Palareti, Gualtiero; Manotti, Cesare; D’Angelo, Armando; Pengo, Vittorio; Erba, Nicoletta; Moia, Marco; Ciavarella, Nicola; Devoto, Gianluigi; Berrettini, Mauro; Leali, Nicoietta; Poggi, Mario; Legnani, Cristina; Musolesi, Serena; Coccheri, Sergio; ISCOAT Study Group (Italian Study on Complications of Oral Anticoagulant Therapy) (Thrombosis and Haemostasis, 1997)
The paper reports on rate and type of thrombotic events occurring during the observational, prospective, inception-cohort, multicenter ISCOAT study. 2,745 unselected, daily practice patients, consecutively referring to 34 Italian anticoagulation clinics to monitor the oral anticoagulant treatment, were included in the study from beginning of their first anticoagulant course. During a total follow-up of 2,011 patient-years of treatment 70 thrombotic events (3.5 per 100 patient years) were recorded in 67 patients: 20 fatal (1%), 39 major (1.9%) and 11 minor (0.6%). 34/70 events occurred within the first 90 days of treatment (relative risk - at multivariate analysis - of <90 days vs. >90 = 20.6, C.I. 12.7-33.5; p <0.0001). The risk was higher in patients aged >70 y (1.62, C.I. 1.0-2.61; p <0.05), and when indication for anticoagulant treatment was peripheral/cerebral arterial disease (1.84, C.I. 1.01-3.36; p <0.05). The frequency of thrombotic events was 17.5% when international normalised ratio (INR) levels were <1.5, decreasing to 2.3% for INRs within the 2-2.99 category (relative risk of INRs <2.0 vs. >2 = 1.88, C.1.1.16-3.07; p <0.05).The recorded rate of thrombotic events was lower than that reported in the few available studies. A greater risk should be expected during the first 90 days of treatment, when anticoagulation levels are <2.0 INR, in patients > 70 years and in those with cerebrovascular/peripheral arterial disease.